Targeted copy number screening highlights an intragenic deletion of WDR63 as the likely cause of human occipital encephalocele and abnormal CNS development in zebrafish. Issue 4 (11th January 2018) - Hofmeister, Wolfgang; Pettersson, Maria; Kurtoglu, Deniz; Armenio, Miriam; Eisfeldt, Jesper; Papadogiannakis, Nikos; Gustavsson, Peter; Lindstrand, Anna
Abstract: Congenital malformations affecting the neural tube can present as isolated malformations or occur in association with other developmental abnormalities and syndromes. Using high‐resolution copy number screening in 66 fetuses with neural tube defects, we identified six fetuses with likely pathogenic mutations, three aneuploidies (one trisomy 13 and two trisomy 18) and three deletions previously reported in NTDs (one 22q11.2 deletion and two 1p36 deletions) corresponding to 9% of the cohort. In addition, we identified five rare deletions and two duplications of uncertain significance including a rare intragenic heterozygous in‐frame WDR63 deletion in a fetus with occipital encephalocele. Whole genome sequencing verified the deletion and excluded known pathogenic variants. The deletion spans exons 14–17 resulting in the expression of a protein missing the third and fourth WD‐repeat domains. These findings were supported by CRISPR/Cas9‐mediated somatic deletions in zebrafish. Injection of two different sgRNA‐pairs targeting relevant intronic regions resulted in a deletion mimicking the human deletion and a concomitant increase of abnormal embryos with body and brain malformations (41%, n  = 161 and 62%, n  = 224, respectively), including a sac‐like brain protrusion (7% and 9%, P  < 0.01). Similar results were seen with overexpression of RNA encoding the deleted variant in zebrafish (total abnormal; 46%, n  = 255, P  < 0.001) compared with the overexpression of an equivalent amount of wild‐type RNA (total abnormal; 3%, n  = 177). We predict the in‐frame WDR63 deletion to result in a dominant negative or gain‐of‐function form of WDR63. These are the first findings supporting a role for WDR63 in encephalocele formation. Abstract : High resolution copy number screening of 66 fetuses with neural tube defects identified six fetuses with likely pathogenic variants (three aneuploidies and three previously reported deletions). We also identified five rare deletions and two duplications of uncertain significance, including a rare intragenic heterozygous in‐frame WDR63 deletion in a fetus with occipital encephalocele. The deletion spans exons 14‐17, resulting in a protein missing the third and fourth WD‐repeat domains. Functional studies in zebrafish support a role for the identified WDR63 variant in encephalocele formation.